Additively manufactured lattice structures for vibration attenuation - Elmadih, Waiel (2020)
Advancements in additive manufacturing technology have allowed the realisation of geometrically complex structures with enhanced capabilities in comparison to solid structures. One of these capabilities is vibration attenuation which is of paramount importance for the precision and accuracy of metrology and machining instruments. In this project, new additively manufactured lattice structures are proposed for achieving vibration attenuation. The ability of these lattices to provide vibration attenuation at frequencies greater than their natural frequency was studied first. This is referred to as vibration isolation. For the vibration isolation study, a combination of finite element modelling and an experimental setup comprising a dynamic shaker and laser vibrometer was used. The natural frequencies obtained from the experimental results were 93 % in agreement with the simulated results. However, vibration attenuation was demonstrated only along one dimension and vibration waves were allowed to propagate, meaning the transmissibility was allowed to be greater than 0 dB. To achieve lower transmissibility, the project demonstrated that lattice structures can develop Bragg-scattering and internal resonance bandgaps. The bandgaps were identified from the lattices' dispersion curves calculated using a finite element based wave propagation modelling technique. Triply periodic minimal surface lattices and strut-based lattices developed Bragg-scattering bandgaps with a normalised bandgap frequency (wavelength divided by cell size) of ~ 0.2. The bandgap of the tested lattices was demonstrated to be tunable with the volume fraction of the lattice unit cell, thus, providing a tool to design lattice structures with bandgaps at required frequencies. An internal resonance mechanism in the form of a solid cube or sphere with struts was designed into the inner core of the unit cell of strut-based lattices. These new internal resonance lattices can provide (a) lower frequency bandgaps than Bragg-scattering lattices within the same design volume, and/or (b) comparable bandgaps frequencies with reduced unit cell dimensions. In comparison to lattices of higher normalised bandgap frequencies, lattices with lower normalised bandgap frequencies have cell sizes that are more suitable for manufacturing with the current additive manufacturing technologies and have higher periodicity within a constrained design volume, resulting in higher attenuation within the bandgaps and more homogenous structures. Similar to the Bragg-scattering lattices, the bandgaps of the internal resonance lattices were demonstrated to be tunable through modification of the geometry of the lattice unit cell. The internal resonance lattice experimentally demonstrated a bandgap of normalised frequency between 0.039 to 0.067 and an attenuation of up to -77 dB. These results are essential for engineering vibration attenuation capabilities within the macro-scale of materials for complete elimination of all mechanical vibration waves at tailorable frequencies. Future work will include further reduction of the bandgap frequencies and increasing the bandgap width by exploring new unit cell designs and new materials for additive manufacturing.